Median Arcuate Ligament Syndrome and Its Associated Conditions. Issue 10 (October 2019) - Huynh, Desmond T. K.; Shamash, Kevin; Burch, Miguel; Phillips, Edward; Cunneen, Scott; Van Allan, Richard J.; Shouhed, Daniel
The risk factors and associated conditions of median arcuate ligament syndrome (MALS) have not been well characterized in the literature. In this study, we aim to investigate the presentation and outcomes of MALS patients with an emphasis on the prevalence of other uncommon disorders. To this end, data of patients with MALS who underwent surgery between 2013 and 2018 were collected and compiled into a retrospective database and analyzed. Eleven patients were identified. Seven of these eleven patients underwent diagnostics to evaluate gastric emptying. Five of these seven patients (71.4%) had radiographic evidence of delayed gastric emptying. Four of the eleven patients (36.4%) were found to have anatomic abnormalities of their visceral vasculature. Two of the eleven patients (18.2%) were found to have connective tissue disorders, both with Ehlers-Danlos syndrome. Three of the eleven (27.3%) had a diagnosis of postural orthostatic tachycardia syndrome. This is the first case series reporting on an association between MALS and delayed gastric emptying. We also explored the relationship between MALS and visceral vascular abnormalities, Ehlers-Danlos syndrome, and postural orthostatic tachycardia syndrome. It is notable that these conditions are more prevalent in the MALS population than in the general population, suggesting a possible pathophysiologic relationship.